(untitled) - I L Finar (London, 1973)
The book offers a comprehensive knowledge of chemical behaviour. It deals with the terms of nomenclatures, preparations (including commercial methods), reactions, and discussions on mechanisms and theoretical aspects. It treats acyclic, alicyclic, aromatic, and heterocyclic compounds. The description of spectroscopic methods has been expanded and the applications of mass spectrometry have been described for many classes of compounds. New material includes enamines, the chemistry of organo-compounds of phosphorus, silicon, boron, and organic photochemistry, including the Woodward-Hoffmann principle of conservation of orbital symmetry
Keywords: chemistry, organic